Evaluation of Small Molecules for Neuroectoderm differentiation & patterning using Factorial Experimental Design - voulgaris, dimitrios (My University, 2016)
Screening for therapeutic compounds and treatments for diseases of the Brain does not only encompass the successful generation of iPS-derived homogenous neural stem cell populations but also the capacity of the differentiation protocol to derive on-demand region-specific cells. Νoggin, a human recombinant protein, has been extensively used in neural induction protocols but its high production costs and batch-to-batch variation have switched the focus to utilizing small molecules that can substitute noggin. Resultantly, the aim of this study was to optimize neuroepithelial stem cell generation in a cost-efficient fashion as well as to evaluate the impact that patterning factors (i.e. small molecules or proteins that enhance the emergence of type-specific neuronal populations) have on the regionality of the neural stem cell population. Findings in this study suggest that DMH1 is indeed a small molecule that can replace noggin in neural induction protocols as previously documented in literature; DMHI appears also to have a ventralizing effect on the generated neural population.
Keywords: Materialvetenskap; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Medicinteknik; Materials Science; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Medical Engineering